MA1S11 (Dotsenko) Solutions to Tutorial/Exercise Sheet 10 Week 12, Michaelmas 2013 1. Evaluate the indefinite integrals √ Z (2 + 3 x)20 √ a) dx x b) Z √ x3 1 + 4x dx √ Solution. a) Let us do the u-substitution u = 2 + 3 x, so that 3 du = √ , dx 2 x and 3 du dx = √ dx, dx 2 x du = making the integral become √ √ Z Z (2 + 3 x)20 2u21 2 2(1 + x)21 20 √ u du = dx = +C = +C x 3 63 63 For b), we use u = 1 + 4x so du = 4 dx, and dx = 14 du. Plus, we have to substitute x = 41 (u − 1) back in to the equation, the equation has x3 in it and 3 x = 1 (u − 1) 4 3 = 1 3 (u − 3u2 + 3u − 1) 64 (1) giving √ Z √ 1 (u3 − 3u2 + 3u − 1) u du = x 1 + 4x dx = 256 Z 1 u9/2 3u7/2 3u5/2 u3/2 = (u7/2 − 3u5/2 + 3u3/2 − u1/2 ) du = − + − +C = 256 1152 896 640 384 (1 + 4x)9/2 3(1 + 4x)7/2 3(1 + 4x)5/2 (1 + 4x)3/2 − + − +C = 1152 896 640 384 Z 3 2. Evaluate the integrals a) Z 0 π/2 sin x dx b) Z 1 2 2 y −y 1 −3 dy and Z 2 1 y 2 − y −3 dy a) is fairly obvious: we know an antiderivative of sin x, that is − cos x Solution. hence π/2 Z 0 sin xdx = − cos x]π/2 = − cos 0 π + cos 0 = −0 + 1 = 1. 2 For b), we know an antiderivative of y 2, it is y 3/3 and of y −3, it is − y 2 , hence 3 2 Z 2 y 1 8 1 1 1 47 2 −3 y − y dy = + 2 = + − − = 3 2y 3 8 3 2 24 1 1 −2 and Z 1 2 2 y −y −3 dy = 1 y3 + 2 3 2y 1 2 3. Evaluate the integrals Z 5 a) (3 + 2w)(3w + w 2 )5 dw = 1 1 8 1 47 + − − =− 3 2 3 8 24 b) −1 Z π/2 cos xesin x dx −π Solution. For a), let us consider the u-substitution u = 3w + w 2 , so that du = (3 + 2w) dw. When w = −1 by substituting back in we have u = −2 and when w = 5, u = 40, hence 6 40 Z 5 Z 40 u 406 − 64 2 5 5 (3 + 2w)(3w + w ) dw = u du = = 6 −2 6 −1 −2 For b) let u = sin x, so that du = cos x dx. When x = −π we have u = 0 and when x = π/2, we have u = 1, giving Z π/2 Z 1 sin x cos xe dx = eu du = eu ]10 = e − 1. 0 −π 4. Evaluate the integral Z 2 −1 Solution. We note that the function integral as Z 2 −1 Z p 2 + |x| dx = = 0 −1 √ p 2 + |x| dx. p 2 + |x| is piecewise defined, and evaluate our 0 −1 Z p 2 + |x| dx + Z 0 2 p 2 + |x| dx = 0 2 2 2 3/2 3/2 2 − x dx + 2 + x dx = − (2 − x) + (2 + x) = 3 3 0 −1 0 √ 2 2 2 2 16 8 √ 2 + 2 3. = − 23/2 + 33/2 + 43/2 − 23/2 = − 3 3 3 3 3 3 Z 2 √ 2 5. Show that Z 2 1/2 1 1 dx = 0 sin x − x x Solution. Let us consider the u-substitution u = 1/x, so that du = − x12 dx, that is dx = − u12 du. We note that for x = 1/2, we have u = 2, and for x = 2, we have u = 1/2, so Z 2 1/2 Z 1/2 Z 2 1 1 1 1 1 1 dx = du, u sin sin x − −u − 2 du = − sin u − x x u u u 2 1/2 u so this integral is equal to its negative, and therefore vanishes. 3